2009
DOI: 10.1042/ba20090179
|View full text |Cite
|
Sign up to set email alerts
|

Efficient expression and secretion of recombinant human growth hormone in the methylotrophic yeast Pichia pastoris: potential applications for other proteins

Abstract: A simple high yielding process for the production of rhGH (recombinant human growth hormone) in the Pichia pastoris system is described. The approach adopted the addition of surfactants during fermentation along with methanol induction. A Pichia integrant harbouring multiple-copy, non-codon-optimized hGH showed poor expression in complex and defined media. Inclusion of the surfactants Tween 20 or Tween 80 during induction enhanced the expression levels significantly in shake flask studies. The combination of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 23 publications
(23 reference statements)
2
7
0
Order By: Relevance
“…A similar result was also obtained by Apte-Deshpande and co-workers [64] for a recombinant P. pastoris strain producing a human growth hormone upon methanol induction. This stimulating effect of surfactants has further been observed in other host organisms including filamentous fungi and bacteria, where authors speculate about a possible correlation with (1) changes in the electrochemical membrane gradients by an altered Na + /K + ratio [65] and (2) an altered membrane stability, even in transport vesicles, leading to enhanced membrane fusion [66].…”
Section: Resultssupporting
confidence: 87%
“…A similar result was also obtained by Apte-Deshpande and co-workers [64] for a recombinant P. pastoris strain producing a human growth hormone upon methanol induction. This stimulating effect of surfactants has further been observed in other host organisms including filamentous fungi and bacteria, where authors speculate about a possible correlation with (1) changes in the electrochemical membrane gradients by an altered Na + /K + ratio [65] and (2) an altered membrane stability, even in transport vesicles, leading to enhanced membrane fusion [66].…”
Section: Resultssupporting
confidence: 87%
“…The authors of these studies suggested that an increase in fluidity of the membrane lipids might facilitate the release of intracellular accumulated protein, thereby enhancing its rate of secretion. The beneficial effect of surfactants, including Tween, appeared to be valid also in other organisms, including cellulase secreting Trichoderma reesei [48], recombinant Schizosaccharomyces pombe [49] and recently also in recombinant P. pastoris [50,51]. Apart from the more apparent explanation of a "leakier" plasma membrane that facilitates translocation of soluble proteins, speculations about the mechanisms underlying this effect also included fluctuations in the electrochemical gradient and enhanced membrane fusions of transport vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…However, production levels were lower than that reported for a hybrid system of somaclonal hairy roots of Nicotiana benthamiana (30–60 μg/g DW) using episomal expression vectors, tobacco cell suspension cultures (0.7 mg/L), maize seeds (5% TSP), tobacco chloroplasts (7% TSP), and rice cell suspension cultures (57 mg/L) . Similarly, production was lower than that reported for microbial and animal‐based systems, such as Escherichia coli (25–100 mg/L), Bacillus subtilis (17–70 mg/L), Pichia pastoris (49–240 mg/L), and Chinese hamster ovary (CHO) cells (4–75 mg/L) . Corresponding, the hGH1 specific productivity obtained for both flask cultures (213 ng hGH/g DW*day) and bioreactor cultures (325 ng hGH/g DW*day) was lower than that reported for other mammalian transgenic proteins; for example, antibodies have been produced by hairy root cultures of Nicotiana tabacum at a specific accumulation rate of 0.22–0.40 mg/g DW*day in both conical flasks and a 2‐L sparged bioreactor, and by whole transgenic plants, in which production ranged from 50 ng/g DW/day to 20 mg/g DW/day …”
Section: Discussionmentioning
confidence: 76%